Plasmonic biosensors: An integrated view of refractometric detection - Dahlin, Andreas B (IOS, 2013)
In this book Andreas Dahlin has written a comprehensive and thorough review of plasmonic biosensors that operate by refractometric detection. After an introductory chapter on biosensors, in which he sets out the concepts of biosensing in its application to such areas as proteomics, medical diagnostics and environmental control, he undertakes an integrated coverage of surface chemistry, surface physics and optics, specifically related to the requirements of design of a plasmonic biosensor. Sections on nanoparticle plasmons and surface plasmons follow, leading to a review of SPR technology for biosensing. The optical properties of nanoholes in metal films and other more complicated plasmonic nanostructures are also briefly discussed. Later chapters discuss experimental plasmon spectroscopy and spectral analysis while the final sections discuss topics such as sensor response and the extent to which quantitative measurements can be made. The book introduces a few relatively controversial opinions on some open questions, such as how best to define sensor performance and the practical use of highly miniaturized sensors. Each of the chapters is extensively referenced and contains appropriate illustrations. The book contains a wealth of information that will be highly beneficial to both existing and new users of refractometric sensing techniques in life science research. It will be a valuable resource for post-graduate research students, academic researchers and those working in industry.